"A woman with a hundred faces": The Dress and Appearance of Anaïs Nin, 1931–1932. (2nd January 2020) - Michel, Gwendolyn M.
Abstract : Author and diarist Anaïs Nin was an important figure in feminist literary circles in the 1960s and 1970s. Her diaries, first published in the 1960s, began with her life in France in the early 1930s. The wife of a banker, she lived a comfortable life, free to pursue her writing and bohemian living, including writing extensively on her use of dress to distinguish herself. This report presents the first in-depth examination of Nin's 1930s diaries and related primary sources from the perspective of dress history and calls for further research into the dress practices of this important literary figure of the twentieth century.